KATNISS’S REBELLION IN THE SUZANNE COLLIN’S THE HUNGER GAMES NOVEL - Shahna Rizkya Balqis; Ayu Melati Ningsih (Fakultas Sastra UMN AL Washliyah, 2022)
This study is propose to reveal find out what kind of rebellion the main character did. The purpose of this study is to analyze rebellion based on inhumanity. And to analyze the rebellion in the novel The Hunger Games (2008). Data collection is by regularly reading novels and understanding the contents of the novel, then finding some existing data. The theory used to analyze the data uses a behavioristic approach theory. After analyzing the data, several reasons and goals of Katniss as the main character in the novel were found in participating in the game event.